A relação da motivação para o trabalho com as metas do trabalhador: um estudo de caso em uma operadora de call center - Salles, Marcos Aurelio (2007)
Having as basic purpose, that the work motivational strategies are more efficient when elaborated directly from the worker¿s personal goals and values, the study line of this dissertation searched to identify the worker¿s motivational employee¿s profile from call center industry. The knowledge of this motivational profile makes possible the development of differentiated programs of motivation inside the organization, aiming to attend goals of diverse groups of workers. In order to achieve the considered objective, the present dissertation analyzed one of the biggest companies in call center¿s inside Brazilian market, the BrasilCenter Communications Ltda. In such a way, in the first stage of the study, a bibliographical research was carried out, with the objective to collect contributions from diverse authors on the motivation subject, and also a modern theory of values was presented, verified empirically in more than 60 countries, which identifies the people¿s motivational structure. Having as base the results of these studies, the worker¿s concept profile motivational and argued its way of evaluation in the organizations it was boarded. In the second stage, a field research was carried out, with the application of the Inventory of Values of Schwartz theory (IVS), in order to identify the employee¿s motivational profile crowded in the Center of Attendance and Services (call center) company, located in Juiz de Fora city. The analysis of the results from the field research, based on the bibliographical data, identified that the values prioritized for the call center¿s employees are the ones that serves the collective and mixing goals. This motivational profile offers some perspectives of employee¿s valuation that correspond to their goals and interests. The displayed results point respect to the centrality of the types of values benevolence, conformity, security and universalism among the participants in the sample. As the accented was more among the employees it was the search of collective results it, is concluded that the more appropriate valuation strategies are those related to the tolerance for the ideas and opinion of the others, to harmonic a organizational enviroment, the concern with the quality of life at work and the social aspects of the work.